(untitled) (Journal of Education Culture and Society, 2020)
Some universities in Central and Eastern Europe are facing a crisis of identity. Academic institutions have for centuries developed independence, liberal education and independent research. Freedom and independence have always been essential for the quality of academic work. Thanks to this , scholars and scientists were restricted only by their own ignorance, which in its turn , was restricted by experience. It meant that the age of the scholar was usually connected to his knowledge. The older scientist had to be smarter and wiser.